PUBLIKASI ILMIAH DAN KARYA INOVATIF GURU GEOGRAFI SEKOLAH MENENGAH ATAS DI KOTA PARIAMAN - Abdul Lathif; afdhal afdhal (JURNAL BUANA, 2020)
This study aims to determine, present, analyze and describe the number of scientific publications and innovative works of high school geography teachers in Pariaman city and to find out what obstacles geography teachers face in the city of Pariaman in making scientific publications and innovative works. This study uses descriptive research with a quantitative approach, the sample in this study consisted of 14 geography teachers in the city of Pariaman, the sample selection was conducted using the total sampling method, which uses the entire total population as a research sample. Data collection techniques used were observation, questionnaires, documentation, literature study. The data analysis technique used is the percentage analysis technique. From the research that has been done shows that, making scientific publications and innovative works of high school geography teachers in Pariaman city is very low, this can be proven from the percentage of scientific publications teachers based on the results of research reports in the field of education (28.6%), based on writing scientific (7.1%), and based on textbook publications (0%) or none of the geography teachers who made them. While the innovative work of teachers has a percentage that is, based on learning media (28.6%), based on the arts in learning (21.4%), based on learning methods (35.7%). This is also caused by the constraints on teachers in making scientific publications and innovative works in the form of a lack of understanding of the ways and procedures for making scientific publications and innovative works, lack of training on scientific publications and innovative works, lack of reading and writing culture from teachers and teacher's lack of motivation in making scientific publications and innovative work. Keywords: Scientific Publications, Innovative Works, Geography Teachers